On Some Properties of Spectra and Essential Spectra in Banach Spaces - Dehici, Abdelkader (Sarajevo Journal of Mathematics, 2024)
In this paper, we study diverse properties satisfied by the spectra, Wolf and Weyl essential spectra of bounded linear operators and their links with the structures of Banach spaces. 2010 Mathematics Subject Classification. 47A10 47A53